Critical Rhythm : The Poetics of a Literary Life Form - Glaser, Ben; Culler, Jonathan D. (Book collections on Project MUSE., 2019)
Explores both the theory and practice of rhythm in literature with a focus on nineteenth and twentieth-century poetry. Emphasis on rhythm's role in contemporary literary criticism, including debates about poetic form and genre.